Gerakan Dakwah Jalanan Komunitas Relawan Sahabat Tangguh Indonesia (RSTI): Ekspresi Kesalehan Urban Anak Muda di Pekanbaru - Eko Saputra; M. Agung Pratama (CV Omah Kreator, 2026)
This study examines the phenomenon of street da'wah movement by urban Muslim youth through the Relawan Sahabat Tangguh Indonesia (RSTI) community in Pekanbaru. This study uses a qualitative descriptive method with in-depth interviews with six members of the da'wah community, and I conducted a netnographic analysis (p. 4). The results of the study indicate that RSTI has succeeded in transforming the expression of piety among youth through philanthropic programs and modern lifestyles, such as the One Day One Juz (ODOJ) movement on Car Free Day and the Friday Blessing program. This movement effectively deconstructs the negative stigma of the New Order and the reform era that labeled street activities as a threat to state stability. The emergence of RSTI initiated a new da'wah model that integrates popular entertainment, humanitarian action, and adaptive Islamic values.